Continuous beer fermentation diacetyl as a villain - Pires, Eduardo J. (2015)
This work tested the viability of producing beer of good quality after maturation of green beer obtained by primary continuous fermentation of high-gravity wort using an airlift bioreactor with flocculated biomass. Fermentation performance of the tested setup was unique as it reached a maximum saccharide consumption rate of 9.43 g L1 h1 and an ethanol productivity of 3.75 g L1 h1. Despite the high levels of diacetyl present in the green beer, a regular maturation was able to reduce it to below threshold values in up to 15 days. It was observed that diacetyl production was strongly correlated with wort composition injected into the system, rather than with the large amount of biomass immobilized in the bioreactor (up to 727 × 106 cell mL1). Organoleptic tests showed that the maturated beer had no major defects.